The Protective Mechanism Against COVID-19, Antibody vs Cellular Immunity: An Extensive Review - Shrwani, Khalid; Dhayhi , Nabil; Mahallawi , Waleed; Sherwani , Alaa; Badedi , Mohammed; Aldossari , Saeed; Muhajir , Abdulrahman; Hassan, Zeinab; Sherwani , Nouf; Karar, Dr. Tarig; et al. (International Journal of Innovative Research in Medical Science, 2023)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has posed a significant threat to the world, causing a respiratory illness with a wide range of symptoms and affecting people of all sexes and age groups. Although the innate immune response to SARS-CoV-2 is not entirely understood, recent findings suggest that a high number of innate immune cells and inflammatory cytokines can help in fighting the virus. However, an excessive expression of cytokines can lead to a cytokine storm, resulting in a severe disease state with high morbidity and mortality. The coordinated actions of the innate and adaptive immune responses are responsible for eliminating virus-infected cells and inhibiting reinfection. The actual role of T-cell immunity and antibody responses is unclear, and further research is necessary to gain insights into the nature of immune protection. The SARS-CoV-2 S protein is considered a sensitive and useful protein that can be targeted by antibodies and T cells, providing significant biological targets for finding effective vaccines and treatments. Despite challenges in developing effective vaccines, the small number of reinfections suggests that a primary infection may offer some protection during subsequent exposure to the same virus. A deeper understanding of the vital role of B and T cells in COVID-19 may help in managing, controlling, and halting this new pandemic.